MODEL PEMBELAJARAN BIPA BERMUATAN KEARIFAN LOKAL ACEH MELALUI MEDIA AUDIOVISUAL MENGGUNAKAN MAKE E MATCH - M. Ade Syahputra; Nasution, Jamaluddin; Kamaruzzaman; Shalawati; Neny Hutagalung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to understand the value of traditional activity videos for BIPA students in terms of the use of audiovisual media with local cultural content. This article discusses the use of traditional activity videos in Aceh as a learning medium for junior secondary BIPA students. This research was carried out using descriptive qualitative methods with the Make E Match research design. This research focuses on traditional culture that still continues today in Aceh. Researchers found that the video seemed significant to students' understanding of traditional culture in Aceh, especially the Peuseujeuk tradition through the speaking and writing practices they had carried out in the BIPA class. Although it is still lacking in terms of affixes, formal and informal context, punctuation and conjunctions, as well as understanding meaning. This article concludes that based on the results of these findings, further research on this topic is needed to improve BIPA teaching and learning, especially in lower secondary level classes.